The diagnostic performance of mid-upper arm circumference (MUAC) for detecting thinness in adolescent girls - Siti Budi Utami; M. Primiaji Rialihanto; Martha Puspita Sari (AcTion: Aceh Nutrition Journal, 2026)
Undernutrition in adolescent girls is a critical aspect of the malnutrition cycle. While early detection is necessary, the standard BMI-for-Age Z-Score (BAZ) method is difficult to implement in community screenings. This study aimed to evaluate the performance of Mid-Upper Arm Circumference (MUAC) in detecting thinness (BAZ < -2SD) in adolescent girls. This school-based cross-sectional study, conducted in 2025, involved 298 female students aged 15-17 years in Yogyakarta. Spearman’s rank correlation was used to test the relationship between MUAC and BAZ, Receiver Operating Characteristic (ROC) analysis was used to determine diagnostic accuracy, and the Youden Index was used to determine the optimal cutoff. The results showed that MUAC had a highly positive correlation with BAZ (r = 0.907, p < 0.001) and excellent predictive accuracy (AUC= 0.972;95% CI: 0.951–0.993). The optimal MUAC cutoff was < 20.7 cm, achieving a perfect sensitivity of 100% and a specificity of 88.3%. Therefore, MUAC is an accurate and effective screening tool for predicting thinness in adolescent girls (15-17 years). The cutoff of 20.7 cm is applicable to this specific population. For national applications, further research expanding the scope to rural locations and a wider age range is highly recommended.